A comparison between the Supreme laryngeal mask airway and the laryngeal tube suction during spontaneous ventilation: A randomized prospective study - Mostafa Somri; Luis Gaitini; Ibrahim Matter; Naser Hawash; Octavio Falcucci; Gustavo Garcia Fornari; Pedro Charco Mora; Swaid Forat; Sonia Vaida (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: The Supreme laryngeal mask airway (SLMA) and the laryngeal tube suction-disposable (LTS-D), both second-generation supraglottic airway devices, have a record of efficiency when used for airway management in mechanically ventilated patients, during general anesthesia. There is no published data comparing these two devices in patients breathing spontaneously during general anesthesia. Material and Methods: Eighty patients with normal airways undergoing elective general anesthesia with spontaneous ventilation were randomized to airway management with a SLMA or LTS-D. Efficacy and adequacy of oxygenation and ventilation were compared. Results: No cases of desaturation of oxygen saturation (SpO2) values of less than 95% occurred with either device. The mean difference for SpO2between the two devices (0.7%) has no clinical significance. Slight hypercapnia was noted with both devices to acceptable values during spontaneous ventilation. Conclusions: Both SLMA and LTS-D are suitable and effective for airway management in patients breathing spontaneously during general anesthesia for minor surgery of short duration.